Arthroscopic Bony Bankart Repair Using Double-Threaded Headless Screw: A Case Report - Takeshi Kokubu; Issei Nagura; Yutaka Mifune; Masahiro Kurosaka (Case Reports in Orthopedics)
We present a case of arthroscopic fixation for bony Bankart lesion using a double-threaded cannulated screw. A 39-year-old man sustained a left shoulder injury from a motorcycle accident. Radiographs showed bony Bankart lesion and CT revealed 40% defect of glenoid articular surface. Arthroscopic fixation was performed using double-threaded cannulated screw after the bony fragment was reduced by suturing the labrum at the edge with a suture anchor. Arthroscopic bony Bankart repair using double-threaded cannulated screw fixation is effective because compression force could be applied between bony fragments and the screw head is not exposed in the glenohumeral joint.